1998
DOI: 10.1165/ajrcmb.19.4.2979
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lumican in Human Lungs

Abstract: The collagen-elastin-proteoglycan (PG) matrix is the key constituent of lung parenchyma and plays a major role in the mechanical behavior of lung tissues. However, the exact composition of the PG matrix in lungs has not yet been fully determined. In the present study we report the expression of leucine-rich repeat PGs in adult human lungs. PG extraction was performed on peripheral lung tissue from patients undergoing therapeutic lung resections. The samples were analyzed by sodium dodecyl sulfate-polyacrylamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…Immunoblotting for lumican (Fig. 5C) revealed multiple diffuse bands predominantly from 50 -100 kDa, indicative of a proteoglycan form of lumican (33)(34)(35)(36). Consistent with the analysis of the MS signal intensities, there was significantly (p Ͻ 0.01) more lumican present in the intima of the atherosclerosis-prone internal carotid artery than in the atherosclerosis-resistant internal thoracic artery, with the mean value elevated by ϳ3-fold.…”
Section: Fig 2 Removal Of Thickened Intima For Proteomic Analysissupporting
confidence: 72%
“…Immunoblotting for lumican (Fig. 5C) revealed multiple diffuse bands predominantly from 50 -100 kDa, indicative of a proteoglycan form of lumican (33)(34)(35)(36). Consistent with the analysis of the MS signal intensities, there was significantly (p Ͻ 0.01) more lumican present in the intima of the atherosclerosis-prone internal carotid artery than in the atherosclerosis-resistant internal thoracic artery, with the mean value elevated by ϳ3-fold.…”
Section: Fig 2 Removal Of Thickened Intima For Proteomic Analysissupporting
confidence: 72%
“…Decorin, biglycan and lumican are small proteoglycans which interact with fibrillar collagens, participating in the maintenance of the extracellular milieu [39][40][41]. In vitro studies have indicated that fibroblasts from COPD patients present abnormal production of proteoglycans and altered expression of the transforming growth factor (TGF)-b Smad pathway when exposed to cigarette smoke or different cytokines [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…10 Lumican belongs to the family of small leucine-rich repeat keratan sulfate proteoglycans (SLRPs) and is one of 10 members of SLRPs found in the lungs. 11 Many members of SLRPs (eg, decorin, lumican, biglycan) play roles in tissue morphogenesis during embryonic development and in adults through their matricellular functions as regulator of collagen fi brillogenesis. [12][13][14] A previous study has shown that lumican increased human corneal epithelial cell migration through the extracellular signal-regulated kinase (ERK) 1/2 pathway.…”
Section: Reduction Of Vili In Lumican-defi Cient Micementioning
confidence: 99%